Perancangan Model Dashboard dan Visualisasi Data Untuk Monitoring Pelayanan Kesehatan di Puskesmas Ballaparang Kota Makassar - hatma hatma; Alfiah Ramadhani Amran; Rini Damayanti (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Puskesmas are the frontline of primary healthcare services that generate a large amount of data related to patient visits, types of diseases, drug availability, and public health performance. However, this data is often not processed and presented effectively, making it difficult for puskesmas management and health departments to monitor and make quick and accurate decisions. This study aims to design an interactive dashboard and data visualization model to facilitate the monitoring of healthcare services at puskesmas. This dashboard model will visually display key performance indicators (KPIs) such as visit statistics, disease trends, and program effectiveness in one easy-to-understand interface. The research method used is a design and development method with a User-Centered Design (UCD) approach, where the needs of users (puskesmas management and staff) are the main focus. The research stages include (1) literature study and needs analysis, (2) designing the dashboard model using data visualization tools, (3) implementing a prototype, and (4) evaluating the model through user testing. The results of this study are expected to be a dashboard prototype that can present health data comprehensively, intuitively, and in real-time, thereby supporting the improvement of efficiency and quality of healthcare services at puskesmas